Correlation between Platelets Count and C-reactive Protein in COVID-19 Patient in Jember Regency - Rini Riyanti; Faliqul Bahar Muhammad; Adelia Handoko (Indonesian Association of Clinical Pathologist and Medical laboratory, 2023)
The laboratory test for Coronavirus disease 2019 (COVID-19) is very important for initial treatment and predicting the prognosis of the patients, but there have been reports of false negative COVID-19 diagnostic test results. Another study reported changes in COVID-19 patient biomarkers, namely platelets count and C-Reactive Protein (CRP) levels. This study investigated the correlation between platelet count and CRP in COVID-19 patients. This study was conducted using a cross-sectional analytic observational method, through secondary data analysis of COVID-19 patients who hospitalized between June – August 2021 at Dr. Soebandi Hospital and Jember Klinik Hospital. Of 30 patients, there were 16 male patients (53%) and 14 female patients (47%); 18 patients in the 46-59 years old age group (60%) and 12 patients in â‰¤ 4 years old (40%) age group; and there were 8 patients admitted to ICU (26.67%). There was a negative correlation between platelet count and CRP in COVID-19 patients (r = -0.733; p<0.001). A strong correlation between platelet count and CRP is related to prognostic and predictive factors of severity in COVID-19 patients. Further studies about the analysis of other biomarkers in COVID-19 are needed to obtain more prognostic and predictive factors of severity in patient.